The Theory of Microhistory in the Scientific Discourse As a Potential Fighting Tool In Hybrid War - Wiktor Możgin; Isabela de Andrade Gama (International Society of Philosophy and Cosmology, 2021)
The article presents the theory of microhistory, taking into account its development, criticism and importance in the field of scientific research. The authors present an analysis of contemporary discourse in the social sciences and humanities, which consists in indicating the need to use methodologies related to the implementation of research on a specific place, process, object. The role of microhistory is to ask big questions in small places, which allows general conclusions to be drawn through the inductive procedure. The authors inscribed this in the context of the hybrid war into which the Ukrainian state was drawn. The authors confirm that getting to know the theory of microhistory, its thorough analysis, and, above all, its practical use in the scientific discourse, through the implementation of research in small Ukrainian towns, will allow you to learn about authentic social moods. From the perspective of events in the eastern regions of Ukraine, the application of scientific achievements (microhistory) will allow us to learn the actual state of the state taking into account all the smallest details, because this is the main goal of the theory of microhistory.